Development of the interurban service by use of alternative commercial road trains - Pocklad, Oleg (Transport, 2007)
The main task of this paper is to review the principal aspects in organization of interurban long haul service by use of road trains on the basis of the “district” traffic system. The goal of the paper is to determine the most effective methods of trucking operations in order to highlight the regularities that characterize these methods. The paper describes practicable methods of freight flow analysis, some factors and parameters concerning movement of motor‐vehicle trains and original route schedules as well. Of special interest is the obtained algorithm of economically effective trucking operations of motor‐vehicle trains on the route.First Published Online: 27 Oct 2010